Spatiotemporal Organization of AT- and GC-rich DNA and Their Association With Transition Proteins TP1 and TP2 in Rat Condensing Spermatids - Kolthur-Seetharam, Ullas (Histochemical Society, 2009)
Transition protein 1 (TP1) and TP2 replace histones during midspermiogenesis (stages 12–15) and are finally replaced by protamines. TPs play a predominant role in DNA condensation and chromatin remodeling during mammalian spermiogenesis. TP2 is a zinc metalloprotein with two novel zinc finger modules that condenses DNA in vitro in a GC-preference manner. TP2 also localizes to the nucleolus in transfected HeLa and Cos-7 cells, suggesting a GC-rich preference, even in vivo. We have now studied the localization pattern of TP2 in the rat spermatid nucleus. Colocalization studies using GC-selective DNA-binding dyes chromomycin A3 and 7-amino actinomycin D and an AT-selective dye, 4′,6-diamidino-2-phenylindole, indicate that TP2 is preferentially localized to GC-rich sequences. Interestingly, as spermatids mature, TP2 and GC-rich DNA moves toward the nuclear periphery, and in the late stages of spermatid maturation, TP2 is predominantly localized at the nuclear periphery. Another interesting observation is the mutually exclusive localization of GC- and AT-rich DNA in the elongating and elongated spermatids. A combined immunofluorescence experiment with anti-TP2 and anti-TP1 antibodies revealed several foci of overlapping localization, indicating that TP1 and TP2 may have concerted functional roles during chromatin remodeling in mammalian spermiogenesis. (J Histochem Cytochem 57:951–962, 2009)